Seroprevalence of bovine brucellosis in trade cattle slaughtered in Ibadan, Nigeria, from 2004–2006. (2010)
A seroprevalence study was carried out among trade cattle slaughtered at Bodija Municipal Abattoir, Ibadan (southwestern Nigeria) over a period of 3 consecutive years from 2004 to 2006 with a view to determining the breed, sex and age distribution in the seropositivity of bovine brucellosis. In total, 1642 animals were examined for antibodies to Brucella abortus using the Rose Bengal test. Seroprevalences of 6.00 %, 6.17 % and 5.31 % were obtained in the years 2004, 2005 and 2006, respectively but a decrease in 2006 shows no significantdifference (P>0.05). The role of the breed (P>0.05), sex (P>0.05) and age (P>0.05) in the occurrence of the infection was not statistically significant at 5 %, although higher rates were obtained for females and older animals. The trend in the disease over the 3-year period showed that it is endemic in trade cattle slaughtered in Ibadan and the public health implications of this are discussed.